Migraine and the triggering food factors - Martins, Laís Bhering; Azevedo, Joyce Fernandes Menezes; Lima, Daniela Cunha de; Costa, Aline Bárbara Pereira; Teixeira, Antônio Lúcio; Oliveira, Dirce Ribeiro de; Ferreira, Adaliene Versiani Matos (Headache Medicine, 2013)
The migraine is a common and disabling disorder that may be related to several factors, including the diet. It is postulate that there is an association between migraine attacks and intake of certain foods and beverages such as ripened cheese, wine, yoghurt, citrus fruits, beer and chocolate. Other dietary aspects as food additives, starvation and insufficient intake of fluids may also trigger migraine. Although published studies are not conclusive, good clinical practice recommends the analysis of food consumption pattern for identification and control of the intake of specific foods that trigger or exacerbate migraine attacks. Therefore, more studies are needed to clarify the possible association between food and migraine.